2001
DOI: 10.1038/sj.onc.1204475
|View full text |Cite
|
Sign up to set email alerts
|

Down-regulation of MET, the receptor for hepatocyte growth factor

Abstract: The ligand-dependent degradation of activated tyrosine kinase receptors provides a means by which mitogenic signalling can be attenuated. In many cell types the ligand-dependent degradation of the tyrosine kinase receptor Met is completely dependent on the activity of the 26S proteasome (Je ers et al., 1997b). We now show that degradation also requires tra cking to late endosomal compartments and the activity of acid dependent proteases as determined by the e ects of a dominant negative form of dynamin (K44A) … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

14
141
4

Year Published

2006
2006
2017
2017

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 160 publications
(159 citation statements)
references
References 39 publications
14
141
4
Order By: Relevance
“…We also wished to assess whether PRS-110-induced internalization differed from the classical ligand-induced internalization. It is known that upon HGF stimulation MET is endocytosed in clathrin-coated vesicles and directed to early endosome compartments so this was examined (46). As anticipated, our data shows that HGF leads to colocalization of the receptor with early endosomal vesicles (EEA-1 positive).…”
Section: Discussionsupporting
confidence: 58%
“…We also wished to assess whether PRS-110-induced internalization differed from the classical ligand-induced internalization. It is known that upon HGF stimulation MET is endocytosed in clathrin-coated vesicles and directed to early endosome compartments so this was examined (46). As anticipated, our data shows that HGF leads to colocalization of the receptor with early endosomal vesicles (EEA-1 positive).…”
Section: Discussionsupporting
confidence: 58%
“…Ligand-dependent endocytosis of RTKs was the common mechanism of receptor inactivation and recycling [30][31][32][33][34][35]44,45]. Consistent to the study in HeLa cells [35], the binding of HGF to c-Met triggers internalization and redistribution of c-Met to the perinulear compartment in HBEpCs.…”
Section: Discussionmentioning
confidence: 65%
“…It is well established that many transmembrane receptors, such as EGF-R and c-Met, become internalized upon ligand stimulation [30][31][32][33]. It has been reported that upon HGF stimulation, c-Met is rapidly internalized via clathrin-coated vesicles and traffics through an early endosomal compartment, which is independent of the proteasome-mediated degradative pathway [34].…”
Section: Introductionmentioning
confidence: 99%
“…This terminates signalling by sequestering MET from the cytosol and preventing it being recycled by the plasma membrane. Finally, the multivesicular bodies fuse with the lysosomes and MET undergoes proteolytic demolition 88,89 . Seemingly active MET is not polyubiquitylated, and is therefore unlikely to be targeted for degradation by theproteasome 87 ; however, proteasomal destruction of MET can occur in an ubiquitin-independent manner (see below).…”
Section: Regulation Of Met Signallingmentioning
confidence: 99%